Developing the pilots' load measuring system. Issue 2 (4th February 2019) - Jankovics, Istvan; Kale, Utku
Abstract : Purpose: The main purpose of this study is to introduce the pilots' load model and developed concept of load measuring system for operator load management. Design/methodology/approach: In future aeronautical system, the role of operators (pilots and air traffic controllers [ATCOs]) will be in transition from active controlling to passive monitoring. Therefore, the operators' load (task, information, work and mental) model was developed. There were developed measuring systems integrating into the pilot and ATCOs working environment eye tracking system outside measuring equipment. Operator load management was created by using the measurement. Findings: In future system depending on time and automation level, the role of information and mental load will be increased. In flight simulator practice, developed load management method serves as a good tool for improving the quality of pilot training. According to the test results, the load monitoring and management system increase the safety of operators' action in an emergency situation. Research limitations/implications: The developed method were tested in two flight simulators (one developed for scientific investigation and other one applied for pilot training) and ATM management laboratory. Practical implications: By deployment of the develop load monitoring and management system, the safety of aircraft flights and air transport management will be increased, especially in an emergency situation. Social implications: People and society's acceptance of future highly automated system will be increased. Originality value: The analysis focuses on the following: developing operator's load model as improved situation awareness model of Endsley, developing monitoring system integrated into operator's working environment, creating load management system.